Collapse and Revival of n-Photon Coherent States and n-Photon Squeezed Coherent States - Alexanian, Moorad
We introduce the set of n-photon coherent states and the set of n-photon squeezed coherent states and study their collapse and revival and compare their behavior with the collapse and revival of the corresponding zero-photon coherent states and zero-photon squeezed coherent states, respectively. The set of n-photon squeezed coherent states (n = 0, 1, 2, ···) forms a basis of the Hilbert state of photons and may be of some interest. We notice that the presence of a few extra photons in the n-photon states as compared to the corresponding zero-photon states makes a large difference in the behavior of their collapse and revival. This indicates the large effect that a few extra photons make in the n-photon states as compared to the corresponding zero-photon states in their collapse and revival.
Keywords: Physics